Local Energy Supply Possibilities—Islanding Microgrid Case Study. Issue 6 (1st August 2018) - Vokony, István; Kiss, József; Farkas, Csaba; Prikler, László; Talamon, Attila
ABSTRACT: Partially for historical reasons, in low voltage distribution systems there still exist network areas which are not operated and maintained by the authorized distribution system operator (DSO). These subnetworks are usually connected to the synchronous system at a single point. The accountable measurement is solved exclusively at this specific connection point as well. After that point, submeter devices serve as a basis for accounting among users. At these network endpoints voltage related problems arise frequently, because after the connection point, the grid is often in poor condition. There are two common solutions to this problem: (i) to eliminate the subnetwork and substitute it with a conventional system from the medium voltage (MV) to low voltage (LV) transformer endpoint; (ii) to provide an island operation system for consumers at the statutory level. In this article, the necessary service quality is analyzed, constructional and operational requirements are cited, and through on-site measurements, a renewable energy mix optimizer application is introduced. Based on the measurements and operational experience, a calculation method has been established to compare the traditional solution and the island operation possibilities. Using the comparison of network development costs and islanding solution costs, an optimal weight factor can be defined, which can be an effective investment decision support parameter.